Melatih Keterampilan Pedagogi Umum Guru MGMP IPA Jakarta Utara Pasca Covid-19 - Elvianasti, Mega; Maesaroh, Maesaroh; Irdalisa, Irdalisa; Roza, Liszulfah; Anugerah, Devi (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
The Covid-19 pandemic that occurred in almost all countries in the world had a very large impact on the way of life of mankind, including the Indonesian people. The Indonesian government demands that people be able to live side by side with Covid-19 so that since early June 2020 the Indonesian people enter the phase of the new normal era. The Covid-19 pandemic has an impact on decreasing productivity in all sectors, including the education sector. The science teacher who is the main facilitator in science learning has a role to present real learning when learning must be done from home, so that the teacher will experience various difficulties. For this reason, it is necessary to provide strengthening of General Pedagogy Knowledge (GPK) for science teachers. In this service, science teachers are given pedagogy reinforcement, alternative media that can be used, alternative assessments, and making lesson plans that are adapted to the new normal era and how to teach science concepts online. Strengthening this General Pedagogy Knowledge can provide 5 benefits for science teachers, science teachers can determine the right strategies / methods in learning during the new normal era, science teachers can develop alternative assessments during the new normal era, science teachers can develop alternative media that can be used, and science teachers can develop lesson plans that can be used during the new normal era and how to explain science concepts online.